2017
DOI: 10.1186/s13148-017-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA array analysis identifies miR-140-3p, miR-33b-3p and miR-671-3p as potential osteoarthritis biomarkers involved in metabolic processes

Abstract: BackgroundMicroRNAs (miRNAs) in circulation have emerged as promising biomarkers. In this study, we aimed to identify a circulating miRNA signature for osteoarthritis (OA) patients and in combination with bioinformatics analysis to evaluate the utility of selected differentially expressed miRNAs in the serum as potential OA biomarkers.MethodsSerum samples were collected from 12 primary OA patients, and 12 healthy individuals were screened using the Agilent Human miRNA Microarray platform interrogating 2549 miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 61 publications
4
97
1
3
Order By: Relevance
“…A recent screen of 2,549 miRs revealed that miR-140-3p, miR-671-3p, and miR-33b-3p are downregulated in the serum of OA patients compared with healthy individuals, with miR-140-3p and miR-671-3p also downregulated in OA articular cartilage compared with healthy cartilage (137). These results complement previous studies showing reduced miR-140 in OA cartilage and knee synovial fluid (26,43,44,138).…”
Section: Mirs As Biomarkerssupporting
confidence: 84%
“…A recent screen of 2,549 miRs revealed that miR-140-3p, miR-671-3p, and miR-33b-3p are downregulated in the serum of OA patients compared with healthy individuals, with miR-140-3p and miR-671-3p also downregulated in OA articular cartilage compared with healthy cartilage (137). These results complement previous studies showing reduced miR-140 in OA cartilage and knee synovial fluid (26,43,44,138).…”
Section: Mirs As Biomarkerssupporting
confidence: 84%
“…Based on bioinformatics and proteomic analysis, Dimitrios et al indicated that the collaborative networks of miRNAs and proteins were associated with OA pathogenesis [40]. In previous studies, serum miRNA array analysis showed that miR-33b-3p may be used as a potential biomarker for OA [41]. Meanwhile, miR-940 is involved in the inflammatory response of chondrocytes in OA [42].…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profile data in the dataset GSE105027 [18] were downloaded from Gene Expression Omnibus (GEO) database. This dataset was produced on GPL21575 Agilent-070156 Human_miRNA_V21.0_ Microarray 046064 platform.…”
Section: Data Resource and Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirms a previous report of increased miR-155 in OA PBMCs 31 . Ntoumou and colleagues performed a large microarray analysis of OA patient serum 32 . They found a number of miRNAs differentially expressed, including seven which were further validated as biomarkers (using qPCR analysis), each manifesting a receiver operator characteristic area under the curve (ROC-AUC)>0.8.…”
Section: Epigenetics: Noncoding Rnasmentioning
confidence: 99%